Micro-longitudinal conversation analysis in examining co-teachers' reflection-in-action. (November 2018) - Ishino, Mika
Abstract: This study used micro-longitudinal conversation analysis (CA) to examine the process of developing the practical knowledge of a native-speaking (NS) English teacher and a non-native-speaking (NNS) English teacher in co-organizing an English-as-a-foreign-language (EFL) classroom interaction. By analyzing their particular repair operations, this study documented in detail the joint reflection-in-action of the co-teachers. In a 50-minute co-taught lesson in a Japanese EFL classroom, the NS and NNS co-teachers faced difficulties in facilitating the transition of a lesson activity from the students' presentations to the teachers' feedback, because the teachers' short dialogue on the next activity failed to gain the students' attention. However, once the NNS co-teacher repaired his first pair part by changing his spatial orientation, the co-teachers' dialogue drew the students' attention, and they were able to achieve a smooth activity transition. After this joint reflection-in-action moment, the co-teachers learned to rearrange their spatial orientations to facilitate activity transitions for the remainder of the lesson. Based on the aforementioned documentation, this study concludes that CA is effective in examining the reflection-in-action of co-teachers and determining useful pedagogical resources for implementing co-teaching lessons with a detailed documentation of their actual usage in practice.